7.7k views
23 votes
Multiply: (x+a)^2-(x-b)^2+x^2+(a-b)x-ab by (a+b)

User Lukeocom
by
5.6k points

1 Answer

9 votes

Answer:

Explanation:

Step-by-step explanation:the answer is =−a2b2y−ab3y+a2+3ax−b2+bx+x2 how did i get answer:Distribute:

=a2+2ax+x2+−b2+2bx+−x2+x2+(a)(x)+(−b)(x)+−a2b2y+−ab3y

=a2+2ax+x2+−b2+2bx+−x2+x2+ax+−bx+−a2b2y+−ab3y

Combine Like Terms:

=a2+2ax+x2+−b2+2bx+−x2+x2+ax+−bx+−a2b2y+−ab3y

=(−a2b2y)+(−ab3y)+(a2)+(2ax+ax)+(−b2)+(2bx+−bx)+(x2+−x2+x2)

=−a2b2y+−ab3y+a2+3ax+−b2+bx+x2

hopes this help I just when back to my answer on my work and I had got a 100 last year.

User Irfan Nasim
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.